New Trends in Microeconomics Theory - Dubovec, Juraj; Hlacina, Tibor (Communications - Scientific letters of the University of Zilina, 2007)
An economist is a professional paid for making wrong economic decisions… While organising a successful business system we can expect that any small internal or external changes can trigger disproportionate responses within the network of international connections and business perspective of the investors. To assume the future development of economy is a problem, nevertheless the economists are trying to find a way of applying the new knowledge if they want to predict the future of certain situations in the real economic system.